A Survey and Identification of Plant Parasitic Nematodes Associated with Grapevine (Vitis Vinifera L.) in The Regions East of Wadi Al-Ajal (Ubari) Southern Libya - Fadel, Sulaiman; Masoud, Abu Baker; Al-Taraqi, Al Mahdi; Ateeq, Muhammad (Journal of Pure & Applied Sciences, 2024)
This study aims to identify and identify nematodes parasitic on grape plants in the areas east of Wadi Al-Ajal “Ubari” in southern Libya, where it surveyed 14 fields in the spring of 2014. These areas are famous for growing grapes: Al-Abyad, Bin Harith, Al-Hamra, Akhlaif, and Al-Qalaa. I collected 50 soil and root samples, at a 1:1 ratio, from grape bushes whose external appearance indicated a possible nematode infestation. The symptoms were as follows: stunted plants, pale leaves, few in number، small in size, yellowing, and lack of growth. Nematodes were isolated using Berman funnels and sieves, conducted in the Plant Pathology Laboratory, Plant Protection Department, College of Agriculture - Sebha University, Libya. The results indicated the presence of five genera associated with grape plants in the study areas. Four genera belong to the Tylenchida order, which is the root-knot nematode Meloidogyne spp., the canker nematode Pratylenchus spp., the spiral nematode genus Rotylenchus spp., and the genus Helicotylenchus spp., and the prevalence of these genera in the fields was 100%, 35.71%, 35.71%, and 7.14%, respectively, and only one genus belongs to the order Dorylaimida, which is the xiphoid nematode Xiphinema spp. with a prevalence rate of 7.14%. As for the distribution of these genera in the different study areas, and from the results of the inventory, it was found that the spread of the root-knot nematode M. Spp. in all regions, followed by the canker nematode P. Spp. was recorded in most areas except the Qalaa area, followed by the spiral nematode genus R. Spp. ranked third in Al-Abyad, Al-Khalif, and Al-Qalaa. In contrast, the lowest presence was recorded only for the spiral nematode genus H. Spp. and xiphoid nematode X. Spp. in the Akhlif area. Thus, the Akhlif area is the only area where all species parasitic on grape plants were recorded in the study area.